Avaliação das relações pré-aritméticas em crianças e adolescentes com deficiência visual - Costa, Ailton Barcelos da (2019)
This research had the general objective of evaluating mathematical skills of counting and measurement of children and adolescents with visual impairment, being organized in two studies. Initially, a general presentation was made, with the main definitions and citations of researches subsidiary to the Studies. The aim of Study 1 was to identify and analyze the empirical studies on the teaching of mathematical repertoires for people with visual impairment in the national and international scientific literature between the years 2001 and 2016. In the first stage we searched for empirical studies on the teaching of mathematical repertoires for people with visual impairment, from the point of view of Behavior Analysis, however, no article on the subject was found for selection and reading. In the next step, we searched for empirical studies on the teaching of mathematical repertoires for all audiences, from the point of view of Behavior Analysis, and there was a predominance of publications about the teaching of mathematics to students with typical development. In the third step, we searched for empirical studies on the teaching of mathematical repertoires for people with visual impairment, regardless of the approach used. The mathematical content selected in the research was characterized as basic mathematics, being part of the regular curriculum of Elementary School I and few studies involved counting and measurement. No studies on teaching or initial assessment of mathematical skills by Behavior Analysis for visually impaired participants were identified. Study 2 aimed to develop a protocol for assessing mathematical skills of counting and measurement for children and adolescents with visual impairment and to test their application. Twelve people with visual impairment, aged between 5 and 16 years, lived in cities in the interior of the State of São Paulo. The procedure, based on the studies analyzed in the literature review, consisted of a survey of the initial repertoire of the participants, using concrete materials and oral instructions, without the offer of tips. A protocol for recording responses in different tasks was used. The construction and definition of the material happened after a pilot application with a person with low vision and another blindfolded person. In the protocol, the information in the form of a spreadsheet was presented in the following order: material, initial instructions on the material, task to be performed with simple instructions and space for recording the response. The material was composed of wooden cubes, squares of plastic material, and strings stiffened with Liquid White Cola. As results, eight participants had greater ease in measuring activities, two in counting, and two with equal performance in both types of activities. The data also indicate that younger participants, five and six years old, made more mistakes than older participants, regardless of having low vision or blindness. These results may be related to the type of content to which the participants were exposed, since the tasks proposed by the protocol were related to pre-arithmetic skills, considered prerequisites for the learning of complex mathematical skills. The performance of the participants was successful in solving the protocol tasks. The execution of the items suggests that the protocol can undergo changes in future research, with four sessions of 24 attempts, besides the reduction in the size of the cubes and replacement of the strings with other material. As a general conclusion, this research met its overall goal, as it was able to produce a mathematical skills assessment protocol for visually impaired people.